Effects of thiamine on vasopressor requirements in patients with septic shock: a prospective randomized controlled trial - Suttasinee Petsakul (2020)
© 2020, The Author(s). Background: Thiamine, an essential vitamin for aerobic metabolism and glutathione cycling, may decrease the effects of critical illnesses. The objective of this study was to determine whether intravenous thiamine administration can reduce vasopressor requirements in patients with septic shock. Methods: This study was a prospective randomized double-blind placebo-controlled trial. We included adult patients with septic shock who required a vasopressor within 1–24 h after admission between March 2018 and January 2019 at a tertiary hospital in Thailand. Patients were divided into two groups: those who received 200 mg thiamine or those receiving a placebo every 12 h for 7 days or until hospital discharge. The primary outcome was the number of vasopressor-free days over 7 days. The pre-defined sample size was 31 patients per group, and the study was terminated early due to difficult recruitment. Results: Sixty-two patients were screened and 50 patients were finally enrolled in the study, 25 in each group. There was no difference in the primary outcome of vasopressor-free days within the 7-day period between the thiamine and placebo groups (mean: 4.9 days (1.9) vs. 4.0 days (2.7), p = 0.197, mean difference − 0.9, 95% CI (− 2.9 to 0.5)). However, the reductions in lactate (p = 0.024) and in the vasopressor dependency index (p = 0.02) at 24 h were greater among subjects who received thiamine repletion vs. the placebo. No statistically significant difference was observed in SOFA scores within 7 days, vasopressor dependency index within 4 days and 7 days, or 28-day mortality. Conclusions: Thiamine was not associated to a significant reduction in vasopressor-free days over 7-days in comparison to placebo in patients with septic shock. Administration of thiamine could be associated with a reduction in vasopressor dependency index and lactate level within 24 h. The study is limited by early stopping and low sample size. Trial registration: TCTR, TCTR20180310001. Registered 8 March 2018, http://www.clinicaltrials.in.th/index.php?tp=regtrials&menu=trialsearch&smenu=fulltext&task=search&task2=view1&id=3330.